Old age from the view of chilean youth: Exploratory study - Arnold, Marcelo; Thumala, Daniel; Urquiza, Anahí; Ojeda, Alejandra (Última Década, 2020)
This investigation searched for the view that the Chilean youth, in this case university students, have on old age. The work is based on the movements of the gerentological thought which to a great extent emphasizes minusvalias in older people which is a product of their social exclusion and unfavorable cultural context, more than of their physical state or mental condition. These exclusions were the object of an investigation made among Chilean youth, by applying a semantic differential test to 682 university students. The intention of the study was to extend the knowledge of the images that the Chilean university students have of old age and propose, a reflection on some of the consequences that these images can have in our society. The results showed a predominance of negative images that are generalized and projected on old age, those that could be affect the perspective of well-being of present and future of the old aged in an increasing context of population aging and increase of the life expectancies.